Tactical urbanism under discussion for urban development (Research, Society and Development, 2020)
Through an exploratory research with a qualitative approach, the discussion about the growth of cities is outlined, and urban restructuring has been the focus of planning discussions, in which tactical urbanism presents itself as an alternative for people to act on public space, and contributed for these actions to stimulate the human relationship and the care with the city. Faced with a political scenario where the agents that control the production of space and end up suppressing the right to the city, the urban scenario faces the actions of citizens to solve local problems, on a small scale, through actions and interventions that are based on a constant experiment on the site. One aspect of this work is to capture the characteristic of the tactical in the transformation of space, so that citizens perform activities that value the construction of the common. From this article, it was possible to recognize tactical urbanism as a tool to assist urban development and its planning, where the production of public space ensures conditions of social quality of life, promoting care and appropriation of the city.